FAKTOR-FAKTOR MEMPENGARUHI IPM DI KOTA BANJARMASIN - NORMA HAYATI (PPJP Universitas Lambung Mangkurat, 2018)
This study aims to determine the effect of government spending on education, health, and social protection simultaneously and partially to the HDI in the city of Banjarmasin from 2006 to 2016.The results of the research using the analysis showed that the results of R-square of 0.952 can be interpreted that government expenditures in education, health and social protection affect the HDI in the city of Banjarmasin from 2006 to 2016. While partially only in the field of education relevant to IPM city Banjarmasin and health, social protection is not partially relevant to HDI in Banjarmasin city. Keywords: Education, health, social protection, HDI.